Internal Consistency of Event-Related Potentials Associated with Cognitive Control: N2/P3 and ERN/Pe - Rietdijk, Wim J. R.; Franken, Ingmar H. A.; Thurik, A. Roy (PloS one, 2014)
Recent studies in psychophysiology show an increased attention for examining the reliability of Event-Related Potentials (ERPs), which are measures of cognitive control (e.g., Go/No-Go tasks). An important index of reliability is the internal consistency (e.g., Cronbach's alpha) of a measure. In this study, we examine the internal consistency of the N2 and P3 in a Go/No-Go task. Furthermore, we attempt to replicate the previously found internal consistency of the Error-Related Negativity (ERN) and Positive-Error (Pe) in an Eriksen Flanker task. Healthy participants performed a Go/No-Go task and an Eriksen Flanker task, whereby the amplitudes of the correct No-Go N2/P3, and error trials for ERN/Pe were the variables of interest. This study provides evidence that the N2 and P3 in a Go/No-Go task are internally consistent after 20 and 14 trials are included in the average, respectively. Moreover, the ERN and Pe become internally consistent after approximately 8 trials are included in the average. In addition guidelines and suggestions for future research are discussed.